How To Talk When Kids Won't Listen : Dealing With Whining, Fighting, Meltdowns And Other Challenges Of Childhood - Faber, Joanna and King, Julie (London Lagom, 2022)
"Do you struggle with having honest and open conversations with your child? Do you find yourself not knowing what to say when faced with a tricky topic? From homework hassles to temper tantrums, sibling rivalry to bedtime battles, every parent has felt the weight of escalating scenarios and ineffective punishment. How to Talk When Kids Won't Listen is filled with top tips, relatable stories, and forward thinking techniques designed to transform your relationship with your child. As the latest publication in the internationally bestselling How to Talk series, this user-friendly guide sees parenting experts Joanna Faber and Julie King reveal their strategies and show you how to put them into practice in real-life scenarios. Whether you are struggling with digital dilemmas, or life-changing events like divorce, it is no secret that the challenges of parenting change over time. Accessible, helpful, and to-the-point, How to Talk When Kids Won't Listen is the go-to book to help build a better relationship with your child"
Including Index
Keywords: Parent and Child -- Parenting -- Interpersonal Communication in Children